2005
DOI: 10.1002/app.22693
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐structure and characteristics of highly oriented polyoxymethylene obtained by press and biaxial drawing

Abstract: ABSTRACT:The physical structure of oriented polyoxymethylene (POM) drawn in two steps by press drawing and subsequent simultaneous biaxial drawing was studied. The degree of crystallinity, the orientation, and the tensile modulus depending on draw ratio were analyzed. By the press drawing method, the draw ratio reached 6.0, the tensile modulus was 4.5 GPa, and the degree of crystallinity decreased from 70% to 65%. By the two-step drawing of press drawing followed by subsequent simultaneous biaxial drawing, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Although the melt spinning of POM fiber was reported in literature, these studies mainly covered the relationship of the orientation degree, take‐up speed, and mechanical properties. For instance, several studies have reported that the orientation degree of lamellar stacks of POM is proportional to the take‐up speed . In the present study, the POM fiber is produced by melt spinning with a high take‐up speed.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Although the melt spinning of POM fiber was reported in literature, these studies mainly covered the relationship of the orientation degree, take‐up speed, and mechanical properties. For instance, several studies have reported that the orientation degree of lamellar stacks of POM is proportional to the take‐up speed . In the present study, the POM fiber is produced by melt spinning with a high take‐up speed.…”
Section: Introductioncontrasting
confidence: 98%
“…For instance, several studies have reported that the orientation degree of lamellar stacks of POM is proportional to the take-up speed. [45,46] In the present study, the POM fiber is produced by melt spinning with a high takeup speed. A strong shear flow field and orientation on the monofilament during crystallization are imposed.…”
Section: Introductionmentioning
confidence: 99%
“…Takasa et al [140] studied the physical structure of oriented POM drawn in two steps by press drawing and subsequent simultaneous biaxial drawing. In the press drawing, the draw ratio reached 6.0 and the tensile modulus was 4.5 GPa, whereby the degree of crystallinity decreased from 70% to 65%.…”
Section: Highly Oriented Productsmentioning
confidence: 99%
“…The resultant biaxial orientation of molecules can often balance them. Therefore, biaxial drawing, including simultaneous or sequential techniques, is widely adopted for manufacturing polymer thin membranes of PE, PTFE, poly(propylene), poly(ethylene terephtalate) (PET), ,, poly(lactic acid), polyamide, polystyrene, and poly(oxymethylene) . These biaxially drawn membranes are industrially utilized as solar cells or display panels. Sequential drawing facilitate a continuous production line, resulting in superior cost performance; however, simultaneous drawing provides better homogeneity of the mechanical properties due to the radial molecular orientation within the resultant membranes.…”
Section: Introductionmentioning
confidence: 99%